The elephant in the room: changing roles of librarians and library technicians - James, Norene; Shamchuk, Lisa; Koch, Katherine (My University, 2014)
The findings from current research will be presented about what librarians and library technicians would like to see in order to achieve a harmonious balance. This session will be interactive and allow for the audience to share their ideas as to how we can better understand each other’s critical role in creating a compatible environment.
Presented on April 25, 2014 at the Alberta Library Conference (ALC) in Jasper, AB.
Keywords: library technicians; librarians; change; work responsibilities